1991
DOI: 10.1002/qj.49711749706
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of tropical cyclone motion using a barotropic model. II: Motion in spatially‐varying large‐scale flows

Abstract: The motion of an initially symmetric vortex in a spatially‐varying large‐scale flow on a beta plane is investigated using a nondivergent, barotropic numerical model. The calculations extend those carried out for the case of zero basic flow in Part I. The large‐scale flows are provided by meridionally‐varying zonal flows, or single‐mode, stationary, finite‐amplitude planetary waves in a channel. Interest is focused on the evolution of vortex asymmetries and their role in determining vortex motion relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…The correlation coefficients of the fitted and observed beta drift are 0.70 and 0.77 for C x and C y , respectively. By setting the environmental factors to zero, it can be seen that in a resting environment, the beta drift is westward and northward with a magnitude of 1.94 m s À1 and an orientation of 336°, which is consistent with most numerical results [Carr and Elsberry, 1990;Ulrich and Smith, 1991;Smith, 1991;Williams and Chan, 1994;Wang and Li, 1995;Li and Wang, 1996;Wang et al, 1997]. [11] The influences of the environmental factors in equations (1) and (2) can be compared with previous numerical results.…”
Section: Observational Relationship Of Beta Drift With Large-scale Ensupporting
confidence: 78%
See 4 more Smart Citations
“…The correlation coefficients of the fitted and observed beta drift are 0.70 and 0.77 for C x and C y , respectively. By setting the environmental factors to zero, it can be seen that in a resting environment, the beta drift is westward and northward with a magnitude of 1.94 m s À1 and an orientation of 336°, which is consistent with most numerical results [Carr and Elsberry, 1990;Ulrich and Smith, 1991;Smith, 1991;Williams and Chan, 1994;Wang and Li, 1995;Li and Wang, 1996;Wang et al, 1997]. [11] The influences of the environmental factors in equations (1) and (2) can be compared with previous numerical results.…”
Section: Observational Relationship Of Beta Drift With Large-scale Ensupporting
confidence: 78%
“…[8] The impact of large-scale environmental flows on beta drift has been extensively investigated numerically in the 1980s and 1990s without observational verification. Previous studies suggested that environmental factors such as latitude change, vorticity gradient and horizontal and vertical wind shears can interact with the primary TC circulation and then significantly affect the magnitude and orientation of beta drift [Ulrich and Smith, 1991;Smith, 1991;Williams and Chan, 1994;Wang and Li, 1995;Li and Wang, 1996;Wang et al, 1997]. Based on the climatologic beta drift obtained in the previous section, the influences of the environmental factors are examined by calculating vertical shears as the difference of wind speeds (u and v) between 200 hPa and 850 hPa, and horizontal shears and the gradient of relative vorticity (z) from the mean winds averaged over the layer between 850 hPa and 300 hPa.…”
Section: Observational Relationship Of Beta Drift With Large-scale Enmentioning
confidence: 99%
See 3 more Smart Citations